Biodiesel production, characterization, diesel engine performance, and emission characteristics of methyl esters from aphanamixis polystachya oil of Bangladesh - Palash, S.M.; Masjuki, Haji Hassan; Kalam, Md. Abul; Atabani, A.E.; Fattah, I.M.R.; Sanjid, Ahmed (Elsevier, 2015)
This paper presents the prospect of biodiesel derived from Aphanamixis polystachya oil in diesel engine. The study deals with the physicochemical properties of A. polystachya methyl ester (APME) and its blends followed by evaluation of performance and emission characteristics of APME5 and APME10 in a multi-cylinder diesel engine. It has been observed that the properties of biodiesel and its blends are compatible with the ASTM D6751 and ASTM D7467 standards, respectively. It was found that, APME5 and APME10 showed an average 0.9 and 1.81 reduction in torque and 0.9 and 2.1 reduction in brake power (BP), and 0.87 and 1.78 increase in brake specific fuel consumption (BSFC) compared to diesel. In the case of engine emissions, diesel blends of APME gave an average reduction in carbon monoxide (CO) and hydrocarbon (HC) emissions compared to pure diesel. However, APME blends emitted higher levels of nitrous oxide compared to diesel. It was found that APME5 and APME10 could be used as a diesel fuel substitute without any engine modifications. (C) 2014 Elsevier Ltd. All rights reserved.